Physiological-biomechanical aspects of the load development and force implementation in rowing - Roth, W. (FISA Coach, 1991)
"Lactic acid concentration measured after a race [performance] gives no information about when it appeared in the race [performance]." Thus, knowing the lactate level tells you nothing about how it was formed in a performance.